2014
DOI: 10.1016/j.pathophys.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor regulation of intestinal development and inflammation in the pathogenesis of necrotizing enterocolitis

Abstract: Toll-like receptors (TLRs) are a structurally related family of molecules that respond to a wide variety of endogenous and exogenous ligands, and which serve as important components of the innate immune system. While TLRs have established roles in host defense, these molecules have also been shown to play important roles in the development of various disease states. A particularly important example of the role of TLRs in disease induction includes necrotizing enterocolitis (NEC), which is the most common gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 190 publications
(248 reference statements)
0
85
0
3
Order By: Relevance
“…21 In contrast, we found that the TLR9 2848G > A SNP was significantly associated with duodenal ulcer, which might be related to the observation that TLRs are important for healing of the injured intestinal epithelium and for the balance between epithelial proliferation and apoptosis. 22,23 In silico analysis have suggested that the À1237C SNP in TLR9 creates a motif with increased binding affinity to NF-kB, which might be functionally relevant, leading to an increased risk for H. pylori-associated gastric diseases. 16 It might also be possible that the observed modifications in TLR5 and TLR9 may alter the capacity of the stomach epithelia to counteract H. pylori infection and predispose to the more severe forms of the gastroduodenal diseases associated with this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…21 In contrast, we found that the TLR9 2848G > A SNP was significantly associated with duodenal ulcer, which might be related to the observation that TLRs are important for healing of the injured intestinal epithelium and for the balance between epithelial proliferation and apoptosis. 22,23 In silico analysis have suggested that the À1237C SNP in TLR9 creates a motif with increased binding affinity to NF-kB, which might be functionally relevant, leading to an increased risk for H. pylori-associated gastric diseases. 16 It might also be possible that the observed modifications in TLR5 and TLR9 may alter the capacity of the stomach epithelia to counteract H. pylori infection and predispose to the more severe forms of the gastroduodenal diseases associated with this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins include HMGBs (HMGB1–4) with two HMG-boxes, mitochondrial transcription factor (TFAM) with two HMG-boxes, upstream binding factor (UBF) with six HMG-boxes, and SP100-HMG nuclear autoantigen with two HMG-boxes (Stros et al, 2007b). TFAM, a transcription factor for mitochondrial DNA, plays a critical role in maintaining the amount of mitochondrial DNA in a promoter-specific manner (Kanki et al, 2004) or a cAMP-dependent phosphorylation manner (Lu et al, 2013a). In addition, TFAM can be released into the extracellular space during infection and injury, and function as a DAMP to regulate immune and inflammatory responses (Chaung et al, 2012).…”
Section: Introduction and Historical Backgroundmentioning
confidence: 99%
“…The elevated expression of TLR4 in the premature gut is reflective to function of TLR4 exhibits in the regulation of normal gut development [13]. In the premature birth situation, intestinal TLR4 levels remain elevated and activation of TLR4 on the lining of the premature intestine by the Gram negative bacteria that colonize the premature gut leads to a number of deleterious effects, including increased enterocyte apoptosis, impaired mucosal healing and enhanced proinflammatory cytokine release, which in aggregate lead to the development of NEC [14] [15]. Also, the translocation of Gram-negative bacteria through the gut mucosa leads to activation of TLR4 on the lining of the endothelium of the premature bowel mesentery, resulting in a reduction in blood flow and the development of intestinal ischaemia and necrosis [16].…”
Section: Hyper-reactive State Of Premature Intestinementioning
confidence: 99%